Atención pedagógica para los estudiantes con bajo rendimiento académico de primero de bachillerato general unificado - Cordero López, Cristian Fernando (2020)
The present work entitled Pedagogical attention for students with low academic performance of first unified general baccalaureate part of the professional observation of the author, in which it is evidenced that some students have low academic results, a situation that leads them to feel frustrated and with They choose to abandon their studies. Among the possible causes, we have reflected on the pedagogical attention provided by teachers. The theoretical references establish the importance of a good educational pedagogical attention and its influence on the academic performance of the students…..